PENDEKATAN KONTEKSTUAL TERHADAP HADIS - Zainul Zainul (UIN Sumatera Utara Medan, 2018)
“Contectualization of comprehending prophetic traditions (hadith). In understanding hadith, must know the condition of sanad and matan. Exceptly, it must also know the circumstances that were happening when the hadith was issued (background), and then also need to know about the properties of hadith, whether universal, temporal or local. All that is need to get a proper understanding of the hadith”